Effectiveness of Using Youtube Videos as a Guide for Science Practicals for Elementary School Teacher Candidates - Shinta Wijaya; Muhamad Ramli; Riska Latifatul Husna (Jurnal Studi Guru dan Pembelajaran, 2025)
Practical learning activities are an important part of forming the competence of prospective elementary school teacher students. However, in its implementation there are several obstacles such as limited time and facilities needed. As time goes by, technology continues to develop, YouTube is one application that can be used as an alternative to guide practical activities for prospective elementary school teacher students. Although YouTube is widely used for learning media, the effectiveness of using YouTube in this context still needs to be studied in depth, especially from the student's perspective. Therefore, this study uses a descriptive qualitative approach to describe students' experiences and perceptions of using YouTube as a guide for practical activities. The population in this study were students of the 4th semester Madrasah Ibtidaiyah Teacher Education (PGMI) study program, who took courses related to science practicums in the even semester of 2024/2025. The sampling technique used was accidental sampling, namely students who were present and willing to fill out the instrument were distributed. The instrument used in this study was a questionnaire. From the data obtained, students stated that they felt helped by YouTube as a guide for science practicums. The reason put forward by students was that YouTube could help them understand the concepts and steps in practical activities. In addition, students also stated that they still need additional sources of information to clarify and expand their understanding. Although it can help students, there are also difficulties and obstacles experienced by students. These difficulties and obstacles are network connections that are sometimes unstable and wasteful quota consumption. In addition to these 2 difficulties, there are also obstacles experienced by students, namely the use of standard language and several new vocabularies that can confuse students. Therefore, students stated that they need additional sources of information other than YouTube.